Developing the full potential of assigned lands : experiences from a sustained engagement with Comprehensive Land Development Programme (IC NGO Programme series ;, 2006)
Report on the historical context and operational modalities of Comprehensive Land Development Programme initiated by the government of Andhra Pradesh for the livelihood and empowerment potentials of Dalit communities.